Bridging the Digital Divide: A Hybrid Community-Based Health Information System for Rural Empowerment - Diyana, Umay; Ali , Annisa' Luthfiah; Anggraeni, Selvy Dwi; Putri, Rizka Syawalena Wahyu; Humairo, Mika Vernicia (Inovasi Lokal, 2025)
A 6-month simulation of a community-based health information system in a rural area involving 500 participants (health workers, volunteers, community) demonstrated the potential for improved access to health services through technology collaboration and local participation. Active participation reached 80%, with a 20% decrease in infectious disease cases and a 35% increase in pregnant women's participation in ANC programs. The hybrid system (SMS gateway and web application) effectively overcame infrastructure limitations, although 30% of areas still experienced network constraints. Technology resistance in the elderly (15%) and interface complexity (30%) highlighted the need for inclusive design. participant feedback (85%) positive) emphasized the importance of educational and emergency features. This simulation confirmed that the success of CBHIS depends on multisectoral partnerships, continuous training, and policy adaptation. The study recommends integration of the system with government programs and long-term evaluation to ensure sustainability. The findings contribute to the literature on digital health innovations in remote areas, in line with WHO recommendations (2021) and studies on technological inclusion (Brown & Lee, 2021).